1999
DOI: 10.1002/hep.510290619
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and survivial of cirrhotic patients with subclinical cognitive alterations detected by the number connection test and computerized psychometric tests

Abstract: The prevalence and the clinical implications of subclinical cognitive alterations in cirrhotic patients have not been well defined as yet. Therefore, we performed a study to assess the clinical features and the survival of cirrhotic patients with cognitive alterations detected by the number connection test (NCT) and a set of computerized psychometric tests (Scan, Choice1, and Choice2) measuring the reaction times and the percentage of errors in performing specific tasks. Ninety-four cirrhotic patients (aged 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
161
2
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(173 citation statements)
references
References 36 publications
7
161
2
3
Order By: Relevance
“…A Z score less than Ϫ2 was considered abnormal. 13,36 A mean Z score (mZS) was calculated for each patient in order to avoid bias related to multiple comparisons. Changes in the number of abnormal NP tests and in the mZS after 3 months of treatment or follow-up were referred to as ⌬ab-normal NP tests and ⌬mZS, respectively, and served as measures of psychometric change.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Z score less than Ϫ2 was considered abnormal. 13,36 A mean Z score (mZS) was calculated for each patient in order to avoid bias related to multiple comparisons. Changes in the number of abnormal NP tests and in the mZS after 3 months of treatment or follow-up were referred to as ⌬ab-normal NP tests and ⌬mZS, respectively, and served as measures of psychometric change.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12] Finally, it is associated with a poor prognosis. 13,14 Thus, MHE may warrant attempts at treatment.…”
mentioning
confidence: 99%
“…7,10,12,[16][17][18] MHE predicts the development of overt HE and also adversely affects survival as shown by several studies. 7,10,18,[84][85][86][87] Das et al 10 studied the progression of MHE to overt HE in relation to severity of liver dysfunction and found that overt HE were more frequent in patients with MHE and Child-Turcotte-Pugh (CTP) score >6. Hartmann et al 7 found that survival was determined only by CTP score irrespective of presence or absence of MHE.…”
Section: Natural History and Survival In Minimal Hepatic Encephalopathymentioning
confidence: 99%
“…Semi-quantitative analysis of the Tc-99m ECD uptake was performed using the region of interest (ROI) templates. 10 Region of interest templates were drawn on paired regions of both cerebral cortices and unpaired regions in the mid-sagittal image. Mean counts in each ROI of the SPECT image is influenced by various factors, like dose of the tracer injected and time of acquisition from the time of injection.…”
Section: Brain Perfusion Single Photon Emission Computed Tomographymentioning
confidence: 99%
“…3,4 Early detection of MHE is clinically relevant for several reasons. Minimal hepatic encephalopathy impairs daily functioning and health-related quality of life (HRQOL), 5,6 it predicts the development of overt HE, 7,8 it is associated with poor prognosis, 9,10 and these patients experience higher rates of accidents, driving problems, and falls. [11][12][13][14] Furthermore, treatment with lactulose or rifaximin improves cognitive functions as well as HRQOL and driving simulator performance in these patients.…”
mentioning
confidence: 99%